DISEMINASI MINA WISATA SEBAGAI ALTERNATIF PENGEMBANGAN WISATA BAHARI DI DESA KEBINTIK KECAMATAN PANGKALAN BARU KABUPATEN BANGKA TENGAH - Bidayani, Endang; Robin, Robin; Syarif, Ahmad Fahrul (Jurnal Abdi Insani, 2024)
Mina Wisata is defined as the concept of a conservation-based integrated management approach with an emphasis on developing fisheries and marine tourism. The development of the concept of minawisata aims to develop the economy of regional communities based on the integrated use of the potential of marine, fisheries and tourism resources in a particular region. The Community Service Program in Kepolitik Village will focus on outreach activities, FGDs and assistance with alternative marine tourism programs to increase tourist visits. The objectives of this activity are: 1) Partners have not managed the tourist interest area optimally; and 2) Partners do not yet have knowledge regarding the management of tourist interest areas. The implementation of PkM is participatory or involves the community in the PkM stages which will focus on: 1) socialization activities, 2) Focus Group Discussions (FGD) to develop strategic priorities for developing tourist attractions based on local potential, and 3) strengthening the institutional management of tourist attractions as an alternative development Marine tourism. The outputs resulting from this activity are: 1) Increasing the quantity and quality of tourist visits; 2) Increasing community understanding and skills regarding tourism activities; and 3) Increase in community income. Program achievement indicators are: 1) Increased community participation; 2) Increasing community welfare; 3) Increasing community knowledge; and 4) Increasing community independence. As a result of the activities, the Kepolitik Village Government and the community were able to contribute positively to all stages of the activities well. The marine tourism pilot program initiated was cleaning beaches and providing rubbish bins, as well as installing beach volleyball nets.